The Impact Of Covid19 To The Unemployment Rate Among Hospitality Students At University Malaysia Kelantan - Semalatha Siva Kumar; Muhamad Nasrulzakwan Kamal Mohd Khir; Aleea Fatina Che Aziz; Khairunnisa Mahirah Khalil (2021)
The COVID-19 pandemics are large scale outbreaks of infectious diseases that can significantly cause severe economic, social, and political harm. This study aims to examine the relationship between the impacts of COVID19 towards the unemployment rate among hospitality students at Universiti Malaysia Kelantan. In this study, it also discusses the impact of restaurants and hotel industry, impact on the job market for hospitality and job seeking among hospitality undergraduates which then can identify the level of unemployment rate. This study has used the quantitative research approach which involved questionnaire methods for data collection. Descriptive analysis, reliability analysis and Pearson Correlation Coefficient analysis have been applied on the usable data. From the results gained of this study, it will be a reference that will redound to the benefit of society at the moment. The findings of this study could provide a guideline for government and academicians to further extend strategies to satisfy hospitality students.